Aberrant telomere length and mitochondrial DNA copy number in suicide completers - Ikuo Otsuka (Nature Portfolio, 2017)
Abstract Short telomere length (TL) occurs in individuals under psychological stress, and with various psychiatric diseases. Recent studies have also reported mitochondrial DNA copy number (mtDNAcn) alterations under several neuropsychiatric conditions. However, no study has examined whether aberrant TL or mtDNAcn occur in completed suicide, one of the most serious outcomes of mental illnesses. TL and mtDNAcn in post-mortem samples from 528 suicide completers without severe physical illness (508 peripheral bloods; 20 brains) and 560 samples from control subjects (peripheral bloods from 535 healthy individuals; 25 post-mortem brains) were analysed by quantitative polymerase chain reaction. Suicide completers had significantly shorter TL and higher mtDNAcn of peripheral bloods with sex/age-dependent differences (shorter TL was more remarkably in female/young suicides; higher mtDNAcn more so in male/elderly suicides). The normal age-related decline of TL and mtDNAcn were significantly altered in suicide completers. Furthermore, shorter TL and lower mtDNAcn of post-mortem prefrontal cortex were seen in suicide completers compared to controls. This study shows the first association of aberrant telomeres and mtDNA content with suicide completion. Our results indicate that further research on telomere shortening and mitochondrial dysfunction may help elucidate the molecular underpinnings of suicide-related pathophysiology.